FACTORS RELATED TO PRIMARY DYSMENORHORE IN STUDENTS OF MESUJI JUNIOR HIGH SCHOOL 2, MESUJI DISTRICT OGAN KOMERING ILIR 2023 - Titin Fitri Handayani; Sri Handayani (Siklus : Journal Research Midwifery Politeknik Tegal, 2024)
The physiological process of menstruation, which happens periodically in women, has been impacted by reproductive hormones, specifically progesterone and estrogen. Dysmenorrhea, or pain during menstruation, is one of the issues with teenage reproductive health during that time. The purpose of the research was to identify the variables associated with primary dysmenorrhea. This type of study was quantitative, with an analytic survey method and a cross-sectional approach in which the research data used primary data This study used 72 samples to represent the population of female junior high school students. The chi-square test was the data source. The study's findings a correlation between primary dysmenorrhea and physical activity (p value 0.005), menarche age (p value 0.033), and nutritional status (p value 0.044). The incidence of primary dysmenorrhea among female students at SMP Negeri 2 Mesuji in 2023 was shown to be correlated with physical activity, age at menarche, and dietary status. Adolescents should take responsibility for the key modifiable dysmenorrhea causes, like exercise routines and nutritional status, by learning more and adopting a healthy lifestyle.